2001
DOI: 10.1007/s004670100021
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and ethnic patterns of childhood nephrotic syndrome in Yorkshire, UK

Abstract: Against the background of the increasing incidence of many immune mediated childhood conditions, this study aimed to identify recent time trends and ethnic patterns of childhood nephrotic syndrome. A population-based cohort of children (0-15 years) diagnosed according to strict criteria with nephrotic syndrome (NS) was ascertained within the northern UK region of Yorkshire between 1987 and 1998. South Asian ethnicity was assigned based on the child's full name using a dedicated computer algorithm and expert in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
126
5
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(155 citation statements)
references
References 13 publications
10
126
5
7
Order By: Relevance
“…The results suggest that children with asthma were more likely to develop INS regardless of sex, age, urbanization of living area, or parental occupation. The annual incidence of NS in children in the United States and in Europe has been estimated to be 1-7 per 100,000 children (1,23). The present study revealed an incidence rate of 2.76 of 100,000 personyears in the nonasthma cohort and a significantly increased incidence rate of 9.21 of 100,000 person-years in the asthma cohort.…”
Section: Discussionsupporting
confidence: 49%
“…The results suggest that children with asthma were more likely to develop INS regardless of sex, age, urbanization of living area, or parental occupation. The annual incidence of NS in children in the United States and in Europe has been estimated to be 1-7 per 100,000 children (1,23). The present study revealed an incidence rate of 2.76 of 100,000 personyears in the nonasthma cohort and a significantly increased incidence rate of 9.21 of 100,000 person-years in the asthma cohort.…”
Section: Discussionsupporting
confidence: 49%
“…Approximately 12%-15% of children with idiopathic nephrotic syndrome do not respond to oral steroid therapy (1,2). Steroid-resistant nephrotic syndrome (SRNS) is a challenging clinical condition with highly variable outcomes, and 50% of children progress to ESRD within 15 years (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing discovery of genetic podocytopathies is about to redefine the physiopathologic understanding, diagnostic assessment, prognostic judgment, and therapeutic approaches in childhood-onset SRNS. However, the development of evidence-based management algorithms has been hampered by the low incidence of SRNS, which is estimated at 2-4 per million person-years (1).…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic Nephrotic syndrome (INS) affects about 2 per 1 lakh children aged ≤15 years [1,2]. About 10% to 20% of these children are resistant to steroids [1].…”
Section: Introductionmentioning
confidence: 99%
“…About 10% to 20% of these children are resistant to steroids [1]. Response to steroids is associated with a good longterm prognosis [3].…”
Section: Introductionmentioning
confidence: 99%